Aquifers in Nirgal Vallis - Reiss, D.; Jaumann, R. (2002)
The topographic information provided by the Mars Orbiter Laser Altimeter has been used in combination with the Mars Observer Camera imagery to estimate the topographic position of sapping pits and gully heads on the rim of Nirgal Vallis. Hence Nirgal Vallis is understood to be formed by groundwater sapping an aquifer is proposed as water supply. Gullies in the northern rim of Nirgal Vallis as discovered in Mars Observer Camera (MOC) images proof the existence of such an aquifer. Further evidence for sapping in Nirgal Vallis is demonstrated by short hanging tributaries with amphitheater-like heads. The basis of these sapping pits defines the contact of aquifer to aquiclude during the valley formation. The gully heads are much deeper under the local surface and the correlation of their topographic position with the valley depth indicate the subsidence of the groundwater level following the vertical erosion of the valley. This implies the existence of different groundwater tables over time confined by impermeable layers, whereas the gully head level is the most recent groundwater table which still may be erosional active under the conditions of increasing water pressure and ice barrier failure. The occurrence of more than one tilted sapping level at different topographic positions which are time-correlated with the erosional notching of the valley, either indicates different aquifers with lithological aquicludes or a climate controlled subsidence of the permafrost layer acting as confining layer.